STUDENTS’ ABILITY ON WRITING DESCRIPTIVE TEXT USING PICTURE MEDIA IN CLASS X HOSPITALITY 3 AT VOCATION HIGH SCHOOL 4 JAMBI CITY - Irma Kristina; Wennnyta Wennnyta; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2022)
This research design uses quantitative research methods with data collection techniques through tests. Where the population in this study was 293 students with samples taken were students of class X Hospitality 3 with a random sampling technique consisting of 26 students. This research consists of problems, research objectives, research methods, research findings and conclusions. The background of this research doing this research was the writing of students' descriptive texts using picture media. The components analyzed in this study were organization, grammar, vocabulary. In collecting data, this research used a written test instrument. This research analyzed students' writing based on five categories, namely: very good, good, average, fair, poor. The results of this study concluded that 26 students of class X 3 at vocation high school 4 Jambi City at the level of writing descriptive texts got an average score of 31.40 from the results of the tests carried out and according to Harris (1969) the average value was included in the fair category. Meanwhile, the average score for each aspect obtained by students, namely, in the organizational aspect was 2.3, this was included in the fair category, and the grammatical aspect was 1.73 which was included in the poor category and the vocabulary aspect was 1.42 including the poor category.